Stem taper and merchantable volume of three provenances of tropical pines in forest plantations of Veracruz, México - Torres Ávila, Dora; de los Santos Posadas, Héctor Manuel; Velázquez Martínez, Alejandro; Tamarit Urias, Juan Carlos (Instituto de Ecología, A.C., 2020)
In recent years in southeastern Mexico, forest plantations of Pinus caribaea have been established, whose purpose is resin extraction and wood production. Both variables have been positively correlated with morphological characteristics such as the shaft shape. Generally, two expressions are used for the description of the stem profile: form factor and taper. In this sense, the objective of the present study was to build a set equations to estimate the stem taper and merchantable volume of three progenies of tropical pines established in a forest plantation in Las Choapas, Veracruz, as well as assess their differences in the stem profile through the approach of dummy variables. Through the model of the linear combined variable and the use of dummy variables, the effect of the provenances on the form factor was analyzed, finding that the hybrid between Pinus caribaea and Pinus elliotti presents a geometry close to the paraboloid. For taper modelling the Demaerschalk model presented the best performance among the tested structures. The mathematical integration of the Demaerschalk model produces a merchantable volume equation that was simultaneously fitted with the taper expression to generate a compatible taper-volume system. The results indicate that the hybrid is superior in the geometry of the bole and in merchantable volume compared to the other two provenances of Pinus caribaea.